(untitled) (Modern education and development, 2025)
Nazar Eshonqul haqida adabiyotshunoslikda turlicha qarashlar mavjudligi sir emas. Bu adibning shaxsiyati va o‘ziga xos tabiati bilan bog‘liq bo‘lsa kerak. Ijodini kuzatsangiz, davr talablariga “moslashish”, unvon-u martabalar ta’masida laganbardorlik kabi illatlar ko‘zga tashlanmaydi. Va eng muhimi, uning qahramonlari ham aynan shu kayfiyatdagi kimsalardir. Muallif realizmda va modernizmda ham kuchini sinab ko‘rdi, ikkalasida ham o‘quvchi ishonchini oqladi It is no secret that there are different opinions about Nazar Eshanqul in literary studies. This is probably related to the writer’s personality and unique nature. If you observe his work, you won’t notice vices such as "adaptation" to the requirements of the time, and greed for titles and ranks. And most importantly, his characters are also in this mood. The author tried his hand at both realism and modernism, and earned the reader’s trust in both.